SELF-EMPLOYMENT IN INDIA IN THE FACE OF GROWING POPULATION AND UNEMPLOYMENT: HIGHLIGHTING THE UNDERCURRENT DETERMINANTS AT PLAY - Kausar, Anisur Rahman; Bormon, Sayanika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
There has been a pressure on consecutive governments and policymakers to create enough jobs in India so that the workforce of India can be used improved and the population can be self-sustainable by becoming economically strong. The creation of jobs, in addition to safeguarding that the working population becomes economically productive, is also a vital avenue for fighting poverty and lack of proper use of intellectual, manual and skill-based potentials of the individuals. India has come to enjoy a distinct advantage in labour market compared to most developed and less developed countries due to the fast changing age distribution of population. India has experienced fairly consistent changes in the first indicator, especially after the 1991 reforms, but the trend in employment has not revealed any consistent or clear pattern. Though the Periodic Labour Force Survey (PLFS) shows increment in worker to population ratio and narrowing of the gender gap in employment in recent past, the unemployment scenario of India still remains disappointing. The present study aims to analyze the factors leading to unemployment and its impact on the Indian economy. The study focusses on how growing population leads to unemployment. The study makes use of secondary data sources and focusses on the present scenario of unemployment in India. The paper analyzes how an increase in population, poverty, illiteracy, inflation and lack of full employment can lead to a slowdown in the growth of the economy.